The Food For Education program in Bangladesh: an evaluation of its impact on educational attainment and food security - Ahmed, Akhter; del Ninno, Carlo (International Food Policy Research Institute, 2002)
The Government of Bangladesh launched the innovative Food for Education (FFE) program in 1993. The FFE program provides a free monthly ration of rice or wheat to poor families if their children attend primary school. The goals of this program are to increase primary school enrollment, promote attendance, reduce dropout rates, and enhance the quality of education. This paper presents the findings of a recent International Food Policy Research Institute (IFPRI) evaluation of the FFE program that demonstrates the extent to which these goals were met. This evaluation uses primary data collected from multiple surveys covering schools, households, communities, and foodgrain dealers. The authors first examine the performance of the FFE program, showing that it has largely fulfilled its objectives of increasing school enrollment, promoting school attendance, and preventing dropouts. The enrollment increase was greater for girls than for boys. The quality of education, however, remains a problem. Next, they analyze the targeting effectiveness of the program, its impact on food security, and its efficiency in distributing rations. In general, the FFE program targets low-income households. However, there is considerable scope for improving targeting, as a sizable number of poor households remain excluded from the program even while many nonpoor households are included. Furthermore, the evaluation results indicate that the functioning of the current private-dealer-based foodgrain distribution system of the FFE program is not satisfactory.